Proposal for the Development of Tourism Marketing for the Plateau, Central Cundinamarca - Rodríguez Escobar, Germán (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
Tourism in Colombia is an activity that has been featured in regional economy, mostly because it is a source of employment and a production chain motor in the different sectors, both public and private, by articulating trade and service companies such as hotels, restaurants, bars, travel agencies, transportation agencies, craft shops and cultural centers, among others. The proposal begins with diagnosing the environment in the region. There, the factors that promote and boost the tourism potential and the opening of new attractions in each municipality are identified; then, we attempt to articulate into a process the relevant information on ecological, cultural, commercial and business issues, as well as sites of both rural and urban interest and differential services that are of interest to a tourist; finally, we aim to formulate the comprehensive tourism marketing proposal containing a dynamic from the exploitation of the town’s attractions, tourist routes and the discovery of new types of tourism, to communication and promotion.